1994
DOI: 10.1073/pnas.91.16.7404
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of an antibody-catalyzed reaction.

Abstract: Antibody 43C9 accelerates the hydrolysis of a p-nitroanilde by a factor of 2.5 x 10i over the background rate in addition to catalyzing the hydrolysis of a series of aromatic esters. Since this represents one of the largest rate accelerations achieved with an antibody, we have undertaken a series of studies aimed at uncovering the catalytic mechanism of 43C9. The immunogen, a phosphonamidate, was designed to mimic the geometric and electronic characteristics of the tetra- Fig. 1. The data can be fit either to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 29 publications
0
32
0
2
Order By: Relevance
“…At the same time, compelling evidence on the covalent catalytic mechanism of 17E8 remains to be obtained (38,39). Covalent catalysis proceeding through an acyl-abzyme intermediate is a feature of another mAb containing HisH35 in the active center, 43C9 (32)(33)(34). Unlike 9A8, comparative mass spectral analysis of mutants and natural 43C9 species showed that the principal nucleophilic residue is HisL91.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, compelling evidence on the covalent catalytic mechanism of 17E8 remains to be obtained (38,39). Covalent catalysis proceeding through an acyl-abzyme intermediate is a feature of another mAb containing HisH35 in the active center, 43C9 (32)(33)(34). Unlike 9A8, comparative mass spectral analysis of mutants and natural 43C9 species showed that the principal nucleophilic residue is HisL91.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown to participate both in general base and in covalent catalysis (27)(28)(29)(30)(31). In addition, HisH35 is implicated in the stabilization of negative charge in the transition state of esterolysis catalyzed by the 43C9 abzyme and is essential for catalytic activity of this antibody (32)(33)(34). Importantly, mAb 43C9 provides an example of catalysis through a covalent acyl-abzyme intermediate, with another histidine, HisL91, participating as the principal nucleophile.…”
Section: Identification Of Catalytic Residues and Modeling Of The 9a8mentioning
confidence: 99%
“…enzyme catalysis and reports of its involvement in antibodymediated catalysis (see, e.g., [7,[9][10][11]41]). Modification of Lys side chains by methyl acetimidate, and of His side chains (up to " 10 per IgG molecule) by DEP resulted in negligible decreases in catalytic activity and binding.…”
Section: Figure 4 Schematic Diagram Illustrating Possible Roles For Tmentioning
confidence: 99%
“…Chemical modification was targeted at Tyr, Lys and Cys side chains, in view of the kinetically influential ionization observed at pK a " 9, at the side chain of Arg because this has been implicated in the functioning of some other antibody preparations (see, e.g., [7,9,35,41]), and at that of His because of the well known involvement of the imidazole\imidazolium side chain in…”
Section: Group-selective Chemical Modification Of Pca270-29mentioning
confidence: 99%
See 1 more Smart Citation